Improving Learning Outcomes for Volleyball Serving Through PBL in Class X Students of SMK N 1 IDI - Hijria Syahputra (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The general objective of this research is to improve student outcomes through the implementation of Volleyball Learning using Problem-Based Learning (PBL). Additionally, this research is conducted to gain in-depth information about the implementation of Volleyball Learning using PBL. The research design is Action Research. The subjects in this study are 28 students from the Eighth grade at SMK N 1 IDI. This research was conducted over two meetings consisting of two cycles. Each cycle consists of three sessions. The first cycle shows that through actions, students can self-motivate. From this first cycle, the result is 4%, indicating that it is not yet complete. In the second cycle, as a reflection of the first cycle, it also shows that actions improve student learning outcomes. The result of the second cycle is 100%, indicating completion. Based on the results of this research, it can be concluded that: (1) Volleyball Learning using PBL improves student learning outcomes, (2) Volleyball Learning using PBL motivates students and makes them active in participating in the learning process.